Application of microRNA in the therapy of ischemic stroke - I. F. Gareev (Кардиоваскулярная терапия и профилактика, 2019)
Stroke is one of the leading causes of death and disability worldwide. The consequences of a stroke are manifested by deep and persistent clinical symptoms, which largely impose a burden on both the patient and society. Current treatments for ischemic stroke have proven to be inadequate, in part because of an incomplete understanding of the cellular and molecular changes that occur during a stroke. Microribonucleic acids (MicroRNAs) are endogenously expressed ribonucleic acid (RNA) of 18-22 nucleotides in length that suppress gene expression at the post-transcriptional level by binding to the 3'-untranslated region of the messenger ribonucleic acids targets. MicroRNAs are involved in virtually all biological processes, including cell proliferation, apoptosis, and cell differentiation, but also play a key role in the pathophysiological processes that contribute to ischemic damage. Moreover, miRNAs can represent not only potential biomarkers, but also become new therapeutic targets in clinical practice, which again confirms the need for their study. Therapy based on miRNA, includes agonists or facial expressions and inhibitors (antagomirs), which accordingly reduces and increases the expression of target genes. In this review, we summarize the current knowledge of fundamental research in the use of microRNAs in the treatment of stroke. The treatment methods, time windows and dosages for the effective delivery of microRNA-based drugs to the central nervous system are discussed. The effects of microRNA therapy on the main pathological mechanisms of stroke, including oxidative stress, inflammation, apoptosis, angiogenesis, neurogenesis, and the safety of the blood-brain barrier are considered.